Efektivitas Penerapan Metode Penyusutan Aset Tetap Pada Usaha Jasa Biro Travel - Heri Toni Hendro Pranoto; Tjandra Wasesa; Diana Zuhroh; Sutini Sutini; Wiratna Wiratna (AKUNTANSI 45, 2023)
Efforts to apply the fixed asset depreciation method in a company are an important policy, because determining the amount of depreciation expense affects the size of the company's profit and the decisions to be taken in the next operational period.For companies that rely on the use of vehicle fixed assets to generate income, it is more effective to apply the fixed asset depreciation method using the multiple decreasing method, because in the early years of use the assets can be used for more work to obtain income, so that the depreciation of the assets also increases. You will also be charged more in the early years of use.